2002
DOI: 10.1139/x02-092
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and species composition of amphibians, small mammals, and songbirds in riparian forest buffer strips of varying widths in the boreal mixedwood of Alberta

Abstract: Forested buffer strips are left along water bodies after forest harvesting to protect water quality and fish stocks, but little is known about their utility as reserves for forest species in managed landscapes. We report on changes in terrestrial vertebrate communities from pre-to post-harvest in experimentally created buffer strips (20, 100, 200, and 800 m wide) in a boreal mixedwood forest in Alberta, Canada. We trapped anuran amphibians and small mammals and spot-mapped bird territories around 12 lakes (4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 71 publications
1
54
1
Order By: Relevance
“…This is contrary to the results of many other studies in which total avian abundance in buffer strips actually increased post-harvest [10,15,17,[45][46][47]. Post-harvest increases in abundance in buffer strips have been attributed to "crowding in" of individuals of mature forest species displaced from nearby clear cuts [10,17,45]. We did not see a crowding effect in our study, possibly because (1) partial harvesting rendered our buffer strips less suitable for forest interior species; or (2) the area surrounding our cut blocks was not as extensively harvested as elsewhere and displaced birds were able to find suitable habitat elsewhere [16].…”
Section: Breeding Bird Response To Partial Harvestingcontrasting
confidence: 99%
See 3 more Smart Citations
“…This is contrary to the results of many other studies in which total avian abundance in buffer strips actually increased post-harvest [10,15,17,[45][46][47]. Post-harvest increases in abundance in buffer strips have been attributed to "crowding in" of individuals of mature forest species displaced from nearby clear cuts [10,17,45]. We did not see a crowding effect in our study, possibly because (1) partial harvesting rendered our buffer strips less suitable for forest interior species; or (2) the area surrounding our cut blocks was not as extensively harvested as elsewhere and displaced birds were able to find suitable habitat elsewhere [16].…”
Section: Breeding Bird Response To Partial Harvestingcontrasting
confidence: 99%
“…It has been suggested that riparian buffer strips are generally too narrow to provide adequate breeding habitat for forest dependent and interior bird species [10,11], although they may contribute to habitat connectivity [19,22]. Since riparian buffers were originally designed to protect aquatic resources, for which the benefits are clear, and only incidentally upland species and habitats [11], current riparian management objectives might be more appropriately focused on water body protection, the conservation of specific riparian habitat features and species, and the creation of movement corridors for aquatic and terrestrial wildlife [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Riparian zones monitoring is based on measurable attributes describing the riparian zone conditions and their ability to carry out their functions. As example, the longitudinal continuity is important for plant dispersal (Johansson et al, 1996;Hughes, 2003), production of stream insects (Hannon et al, 2002;Whitaker et al, 2000) or migration of birds (Decamps et al, 1987;Tewksbury et al, 2002) and mammals (Darveau et al, 2001;Cockle and Richardson, 2003). Monitoring often combines observable physical, chemical and biological attributes, which can vary in response to human alteration.…”
Section: Introductionmentioning
confidence: 99%